Centralization of Biliary Atresia: Has Germany Learned Its Lessons? - Madadi-Sanjani, Omid; Fortmann, David; Rolle, Udo; Rodeck, Burkhard; Sturm, Ekkehard; Pfister, Eva-Doreen; Kuebler, Joachim F.; Baumann, Ulrich; Schmittenbecher, Peter; Petersen, Claus (European Journal of Pediatric Surgery, 2021)
Introduction The majority of pediatric surgeons and hepatologists recommend the centralization of biliary atresia (BA) treatment within experienced liver units. We aimed to investigate whether voluntary self-restriction and acceptance of the need for this change in practice changed the BA referral policy in Germany during the last decade.Materials and Methods In cooperation with pediatric surgeons, gastroenterologists or hepatologists, and pediatric liver transplant units, the 2-year follow-up data of infants with BA born in Germany between 2010 and 2014 were collected using www.bard-online.com or pseudonymized data transfer. Results were compared with our previous analysis of the outcome data of infants with BA born between 2001 and 2005 in Germany.Result Overall, 173 infants with BA were identified, of whom 160 underwent Kasai portoenterostomy (KPE; 92.5%) and 13 (7.5%) underwent primary liver transplantation at 21 German centers. At 2-year follow-up, overall survival was 87.7% (vs. 81.9% in 2001–2005 [p = 0.19]), survival with native liver post-KPE was 29.2% (vs. 22.8% in 2001–2005 [p = 0.24]), and jaundice-free survival with native liver post-KPE was 24.0% (vs. 20.1% in 2001–2005 [p = 0.5]). Compared with the 2001–2005 analysis, all criteria showed improvement but the differences are statistically not significant.Conclusion Our observation shows that KPE management requires improvement in Germany. Centralization of BA patients to German reference liver units is not yet mandatory. However, European and national efforts with regard to the centralization of rare diseases support our common endeavor in this direction.
Keywords: biliary atresia; Germany; centralization; liver transplantation; registry